The Second Anglo-Boer War: An Overview - Pretorius, Fransjohan (Scientia Militaria - South African Journal of Military Studies, 2012)
Two definite phases can be discerned in the Second Anglo-Boer War of 1899 to 1902: the conventional (setpiece-battle) phase from the outbreak of the war on II October 1899 to the Battle of Dalmanutha (Bergendal) between 21 and 27 August 1900; and the guerrilla phase from September 1900 to the end of the war on 31 May 1902. However, it makes more sense to add a transitional phase, stretching from March to August 1900, which contains characteristics of both major phases. With the conventional phase we specifically mean that period when the two opposing forces were mustered against each other on the battleground and both attempted to defeat or push back the other in a direct confrontation. That is, when the opposing armies both pursued a combat strategy. The nature of the guerrilla phase - marked by a change in the Boer strategy - will be discussed below.